PEMBANGUNAN APLIKASI KLASIFIKASI KODE SURAT BERBASIS ANDROID MENGGUNAKAN ALGORITMA BOYER-MOORE DI KANTOR KECAMATAN CIPARAY - COMPUTING INFORMATIKA; Yusuf Muharam (COMPUTING | Jurnal Informatika, 2021)
(1) Archivist is a term for people who have competence in the field of archives, usually the archivist profession can be found in government offices. One of the archivist's duties is to manage incoming or outgoing records. In these management activities, archivists will perform code matching on archives/letters using a list of archive code classifications that have more than 2000 indexes manually, with that many indexes, of course the code matching performed by archivists is not efficient. The use of Android-based applications can make searching and matching archive code faster and more efficient. For faster application search performance, a special algorithm that matches strings is needed. The string matching algorithm that is still popular today is the Boyer-Moore algorithm, this algorithm is considered to have the best results, because in practice, the algorithm moves to match strings from right to left. This research was conducted by building an application called Android-based Letter Code Classification that can search for archive codes by implementing the Boyer-Moore algorithm as an algorithm that performs string matching. (2) The research method used is the Waterfall method, this method has a systematic and sequential approach to the software development process. (3) After the application development is complete, the application is tested using the black-box testing method and user acceptance testing. Black-box testing is carried out so that the application does not have errors in the interface and performance, while acceptance testing is carried out so that the feasibility level of the application can be assessed directly by the user. (4) It is known that based on the results of black-box testing and assessment tests carried out by users, the application can run smoothly and is considered effective and feasible to use in searching for letter code classifications.